The connection between innervation and metabolic rearrangements in pancreatic cancer through serine - Dong, Mengmeng; Cao, Lidong; Cui, Ranji; Xie, Yingjun (Frontiers in Oncology, 2022)
Pancreatic cancer is a kind of aggressive tumor famous for its lethality and intractability, and pancreatic ductal adenocarcinoma is the most common type. Patients with pancreatic cancer often suffer a rapid loss of weight and abdominal neuropathic pain in their early stages and then go through cachexia in the advanced stage. These features of patients are considered to be related to metabolic reprogramming of pancreatic cancer and abundant nerve innervation responsible for the pain. With increasing literature certifying the relationship between nerves and pancreatic ductal adenocarcinoma (PDAC), more evidence point out that innervation’s role is not limited to neuropathic pain but explore its anti/pro-tumor functions in PDAC, especially the neural–metabolic crosstalks. This review aims to unite pancreatic cancer’s innervation and metabolic rearrangements with terminated published articles. Hopefully, this article could explore the pathogenesis of PDAC and further promote promising detecting or therapeutic measurements for PDAC according to the lavish innervation in PDAC.